Local knowledge in inclusive education policies in Africa: informing sustainable outcomes - Chioma O. Ohajunwa (African Journal of Disability, 2022)
Background: This article presents on the outcomes of a study that focused on an analysis of inclusive education (IE) policies in South Africa, Ghana and Uganda. Persons with disabilities live within communities and are raised by the values that apply within their communal context. Policymaking is intricately linked to policy implementation, and the inclusion of local knowledge strengthens policy influence, impacting on implementation processes.